The value of riparian reserves for nonvolant small mammal conservation in disturbed and converted forest landscapes in Sabah, Malaysia - Nellcy Joseph (2019)
Logging and forest conversion to oil palm plantations are two of the main factors affecting South-East Asia's rich tropical rainforests biodiversity. Retaining forest fragments flanking streams, i.e. the riparian reserves, within disturbed and converted habitat matrix is generally recognized to be useful practice for enhancing biodiversity or mitigating biodiversity loss, although the usefulness of such forest fragments for the conservation of non-volant small mammals is still poorly known. A study was conducted at the Stability of Altered Forest Ecosystem project area (SAFE) located in and around Kalabakan Forest Reserve, in south central part of Sabah, Malaysian Borneo, by using live-cage traps arranged in a grid, to study the non-volant small mammal communities in riparian reserves located within unlogged forests, repeatedly logged forests and in oil palm plantations. To compare the effects of retaining riparian reserves within oil palm plantations, the small mammals were also sampled in the oil palm plantations without any riparian reserves. In this study, the species richness, diversity, abundance and community composition of the small mammals were compared between the different riparian reserve treatments. A total of 1,446 individuals of small mammals were captured over 13,440 trap-nights, represented by 23 species from 3 orders and 5 families at all of the sampling sites combined. The riparian reserves within the logged forest sites (6 sites) recorded an average of 12.33 ± 2.42 (s.d.) species of small mammals, compared to an average of 11.50 ± 0.71 species in the unlogged forest sites (2 sites) and 12.33 ±1.15 species in oil palm plantation sites (3 sites). Sites in oil palm plantation without riparian reserves (3 sites) recorded an average of 7.67 ±1.15 species. Small mammals in unlogged forest sites showed the highest species similarity with the logged forest sites (50rensen similarity coefficient= 45%), while the lowest species similarity was recorded between unlogged forest sites and oil palm plantation without riparian reserve (37%). Although, species richness was higher in logged forest than in unlogged forest, the species diversity (based on Simpson's inverse diversity index) was recorded to be higher in the unlogged forest than in the logged forest. The small mammal species richness and abundance were lower in the oil palm without riparian reserves compared with oil palm with riparian vegetation; and the commensal species, i.e., rats (Rattus exulans and R. rattus), dominated (67% of total individuals caught) the habitat in the oil palm without riparian vegetation. Increase in the understory vegetation appeared to significantly increase the presence of small mammals. Conversely, increase in the bare ground cover decreases the presence of the small mammals. As coverage of understorey vegetation is generally positively associated with foraging and nesting sites for small mammals, as well as refuge sites from predators, the findings of this study generally suggest that retaining riparian reserves in oil palm plantations can help in the conservation of the non-volant small mammal community. This finding may have important implications for future riparian reserves management particularly in oil palm plantation with a view to increase the biodiversity within this converted landscape.